ROLE OF LANGUAGE AS A SOCIAL AND CULTURAL INSTITUTION: A LITERATURE REVIEW (Lectio: Journal of Language and Language Teaching, 2025)
This paper addresses role of language as a social and cultural institution on the basis of literature review or documentary study. Language is defined as a social institution on the basis of premise that there is a close relationship between language and society and the relationship is symbiotic-reciprocal as language exists in society and society exists in language. The relationship is reflected in the features of language used by a society as members of a social group in social contexts in which the meanings stored in the forms of language used comprise an organized system of norms and structures to regulate social life and to maintain solidity, solidarity, stability, and continuity. Language is defined as a cultural institution as there is a close relationship between language and culture belonging to a society as members of a social group. The relationship is symbiotic-reciprocal as language exists in culture and culture exists in language. The role of language as a cultural institution has wider scope because language used by a society as members of a social group serves as a potential resource to uncover various cultural aspects along with its function as an element, index, and symbol of culture.
Keywords: meaningfulness; language; social institution; cultural institution